Low voc environmentally friendly interior wall coating composition and method of making same
Patent Information
- Application Number
- CN202610760044.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-29
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-05-29
AI Technical Summary
[0004]本发明的目的在于提供一种低VOC环保建筑内墙涂料组合物及其制备方法,其解决了现有的低VOC涂料中成膜助剂释放VOC且无甲醛捕捉、分散剂效率低、漆膜耐洗刷性差的技术问题
本发明通过设计并合成N-(二氨基乙基)-氨基丙基甲基二甲氧基硅烷改性甲基丙烯酸缩水甘油酯-聚醚胺-环氧大豆油开环共聚物(改性化合物A)和二乙烯三胺封端超支化聚甘油接枝聚丙二醇二缩水甘油醚星形共聚物(改性化合物B),在不添加挥发性成膜助剂和有机溶剂的条件下,实现了多项性能的协同提升。在环保方面,本发明完全摒弃了醇酯十二等常规成膜助剂,所得产品的挥发性有机化合物含量低,真正解决了“环保性能与使用性能难以兼得”的技术瓶颈;
Abstract
Description
Technical Field
[0001] This invention relates to the field of architectural coatings technology, specifically to a low-VOC environmentally friendly interior wall coating composition and its preparation method. Background Technology
[0002] Interior wall coatings are among the most widely used materials in interior decoration, and their environmental performance directly affects the health of residents and indoor air quality. In recent years, with increasingly stringent national environmental regulations and rising consumer demand for green building materials, the development of ultra-low volatile organic compound (VOC) or even zero VOC interior wall coatings has become an inevitable trend in the industry. Vinyl acetate-ethylene copolymer emulsions and pure acrylic emulsions, due to their ability to formulate low VOC coatings without the need for organic solvents or plasticizers, have become the mainstream base material choices for environmentally friendly water-based interior wall coatings. However, these emulsion systems with low glass transition temperatures typically require the addition of alcohol ester film-forming aids during film formation to promote polymer particle fusion. Traditional film-forming aids, such as dodecyl alcohol ester, slowly evaporate into indoor air during film formation, becoming one of the main sources of VOCs. Simultaneously, the health hazards of formaldehyde gas released from interior decoration materials have attracted widespread attention, making the ability of interior wall coatings to actively capture and decompose formaldehyde a hot research topic in the industry. Furthermore, the dispersion stability of pigments and fillers in coating systems, the washability, stain resistance, and anti-blocking properties of the coating film often fail to reach ideal levels after the removal of traditional volatile additives. Therefore, achieving excellent film-forming properties, efficient formaldehyde purification capabilities, and superior mechanical properties of the coating film without relying on volatile organic compounds has become a pressing technical challenge in this field.
[0003] To address the aforementioned issues, researchers both domestically and internationally have conducted extensive research. Regarding film-forming aid replacements, reactive film-forming aids have been reported, which participate in the cross-linking and curing of emulsion polymers through active groups in their molecular structure, thereby preventing the volatilization of small molecules. However, existing reactive film-forming aids generally lack the ability to actively capture indoor formaldehyde, and their compatibility with the polymer matrix and reaction efficiency still need improvement. In formaldehyde purification technology, amino-functionalized materials have attracted attention due to their ability to undergo irreversible Schiff base addition reactions with formaldehyde. However, effectively introducing polyamine structures into coating systems and maintaining their long-term activity while avoiding negative impacts on coating storage stability and film-forming properties remains a technical challenge. In the field of dispersants, while traditional small-molecule wetting and dispersing agents or linear polymer dispersants can reduce the viscosity of grinding slurries, their dispersion efficiency is limited, and they are prone to migrating and precipitating from the paint film, affecting water resistance and adhesion. Hyperbranched polymers, due to their three-dimensional spherical structure and abundant terminal functional groups, exhibit unique advantages in reducing system viscosity and enhancing crosslinking density. However, there are no systematic reports on their design as multifunctional dispersants that combine pigment anchoring, steric stabilization, and participation in film-forming crosslinking. Furthermore, silane coupling agents can be used in coatings to enhance organic-inorganic interfacial bonding, but their premature hydrolysis and polycondensation in aqueous systems severely limit their practical application effectiveness. Summary of the Invention
[0004] The purpose of this invention is to provide a low-VOC environmentally friendly interior wall coating composition and its preparation method, which solves the technical problems of existing low-VOC coatings, such as VOC release by film-forming aids without formaldehyde capture, low dispersant efficiency, and poor scrub resistance of the paint film.
[0005] The present invention achieves the above objectives through the following technical solutions: A method for preparing a low-VOC environmentally friendly interior wall coating composition, comprising the following steps: S1. By weight, add 20-35 parts of deionized water to a dispersion vessel; under stirring, add 0.5-2.0 parts of diethylenetriamine-terminated hyperbranched polyglycerol-grafted polypropylene glycol diglycidyl ether star copolymer and 0.1-0.4 parts of polyether-modified polysiloxane in sequence, and stir; add 15-25 parts of titanium dioxide, 8-15 parts of calcined kaolin, 5-12 parts of heavy calcium carbonate and 2-5 parts of talc, and grind to obtain pigment and filler slurry; S2. Add 25-35 parts of styrene-acrylic emulsion, 15-25 parts of acrylic emulsion, and a mixture containing 2.0-6.0 parts of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane-modified glycidyl methacrylate-polyetheramine-epoxy soybean oil ring-opening copolymer and 3-5 parts of methyl isobutyl ketone to the pigment and filler slurry. Stir, add 0.3-1.2 parts of associative polyurethane thickener and 0.1-0.4 parts of 2-amino-2-methyl-1-propanol, adjust the pH to 8.0-9.5, add 0.1-0.4 parts of polyether-modified polysiloxane and 0.1-0.3 parts of 1,2-benzisothiazolin-3-one, stir, and degas.
[0006] The preparation reaction mechanism of the low-VOC environmentally friendly building interior wall coating composition in this invention is as follows: In the preparation stage of pigment and filler slurry, deionized water is added to a dispersion vessel, and diethylenetriamine-terminated hyperbranched polyglycerol-grafted polypropylene glycol diglycidyl ether star copolymer is added as a high-efficiency dispersant, along with polyether-modified polysiloxane. Subsequently, titanium dioxide, calcined kaolin, heavy calcium carbonate, and talc are added. The polyamine groups on the periphery of the star copolymer are firmly anchored to the surface of the powder particles through interaction, and the long arms of the polyether extend into the aqueous phase to construct a steric barrier. After grinding, a highly stable inorganic powder suspension is created. Film-forming base materials styrene-acrylic emulsion and acrylic emulsion are added to it, as well as a mixture containing N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane-modified glycidyl methacrylate-polyetheramine-epoxidized soybean oil ring-opening copolymer and methyl isobutyl ketone. Next, an associative polyurethane thickener is added to weave a dynamic three-dimensional rheological network within the liquid phase. 2-Amino-2-methyl-1-propanol is added to adjust the pH to ensure emulsion stability. Polyether-modified polysiloxane is added for degassing, and 1,2-benzisothiazolin-3-one is added for corrosion protection. During coating application and film formation, moisture evaporates, emulsion particles fuse to form a film, and the dimethoxysilyl groups on the side chains of the ring-open copolymer hydrolyze to generate silanol groups, undergoing dehydration condensation and self-crosslinking. Simultaneously, the densely packed free amine groups in its backbone actively capture formaldehyde molecules from the environment through nucleophilic addition reactions, curing to form a low-VOC environmentally friendly interior wall coating composition with air-purifying functions.
[0007] According to a preferred embodiment of the present invention, in step S1, the grinding time is 30-40 minutes.
[0008] According to a preferred embodiment of the present invention, in step S2, the degassing time is 15-20 min.
[0009] According to a preferred embodiment of the present invention, the preparation method of the N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane modified glycidyl methacrylate-polyetheramine-epoxidized soybean oil ring-opening copolymer includes: A1. By weight, mix 80-120 parts of epoxidized soybean oil and 100-150 parts of polyetheramine, and react at 110-120℃ under nitrogen protection; cool to 80-90℃, add 0.02-0.10 parts of phenothiazine and 0.2-1.0 parts of triphenylphosphine, and dropwise add 20-40 parts of methyl isobutyl ketone containing 15-25 parts of glycidyl methacrylate, and continue the reaction at 80-90℃ to obtain a mixture; A2. Add 10-20 parts of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane and 40-60 parts of methyl isobutyl ketone to the mixture and react at 60-80℃; then distill under reduced pressure.
[0010] In this invention, the preparation reaction mechanism of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane-modified glycidyl methacrylate-polyetheramine-epoxidized soybean oil ring-opening copolymer is as follows: Under nitrogen protection, epoxidized soybean oil and polyetheramine are mixed and heated. The primary amine groups at the end of the polyetheramine exhibit strong nucleophilicity, launching a nucleophilic attack on the epoxy groups in the epoxidized soybean oil, causing the epoxy groups to undergo a ring-opening reaction, transforming into secondary amine and secondary hydroxyl structures, thereby forming a prepolymer. After cooling, phenothiazine and triphenylphosphine are added, and methyl isobutyl ketone containing glycidyl methacrylate is added dropwise. Methyl isobutyl ketone serves as the reaction medium; phenothiazine captures trace free radicals to prevent the double bonds from self-polymerizing upon heating; triphenylphosphine polarizes the epoxy groups, prompting the residual free amine groups on the prepolymer backbone to launch a nucleophilic ring-opening attack on the epoxy groups of glycidyl methacrylate, connecting the backbone with double bonds to the main chain, resulting in a mixture. Finally, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane and methyl isobutyl ketone were added to the mixture. The amino group in the N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane molecule underwent a Michael addition reaction with the methacrylic acid double bond on the side chain. The amino group nucleophilically attacked the unsaturated double bond, and finally synthesized the N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane modified glycidyl methacrylate-polyetheramine-epoxidized soybean oil ring-opening copolymer with a specific structure.
[0011] According to a preferred embodiment of the present invention, in step A1, the reaction continues at 80-90°C for 3-5 hours.
[0012] According to a preferred embodiment of the present invention, in step A2, the reaction time at 60-80°C is 3-5 hours.
[0013] According to a preferred embodiment of the present invention, the preparation method of the diethylenetriamine-terminated hyperbranched polyglycerol-grafted polypropylene glycol diglycidyl ether star copolymer includes: B1. By weight, add 0.3-0.8 parts pentaerythritol and 0.02-0.10 parts sodium methoxide to a reaction vessel. Under nitrogen protection, heat to 95-100℃, add 10-15 parts glycidyl ether dropwise, heat to 100-105℃ for polymerization, add 5-10 parts methanol to obtain a hyperbranched polyglycerol core; activate 1.0-2.5 parts of the hyperbranched polyglycerol core with 0.02-0.10 parts potassium hydroxide in 15-25 parts dipropylene glycol dimethyl ether, and add dropwise to 15-25 parts polypropylene glycol diglycidyl ether preheated to 85-95℃ to obtain an intermediate; mix 5-8 parts diethylenetriamine and 8-15 parts propylene glycol monomethyl ether, heat to 55-65℃ to obtain a diethylenetriamine solution; add the intermediate dropwise to the diethylenetriamine solution and continue the reaction to obtain a reaction mixture; B2. Add deionized water to the reaction mixture and adjust the pH with glacial acetic acid.
[0014] In this invention, the preparation reaction mechanism of diethylenetriamine-terminated hyperbranched polyglycerol grafted polypropylene glycol diglycidyl ether star copolymer is as follows: The initial reaction uses pentaerythritol as a divergent initiator. Under the catalysis of sodium methoxide, some hydroxyl groups of pentaerythritol lose protons and transform into highly reactive oxygen anions. The addition of glycidyl ether initiates anionic ring-opening polymerization, forming an increasing number of terminal hydroxyl groups. Finally, methanol is added to terminate the reaction, quenching excess active centers and yielding a hyperbranched polyglycerol core. Subsequently, the hyperbranched polyglycerol core is pre-activated with potassium hydroxide in dipropylene glycol dimethyl ether, restoring the strong nucleophilicity of its surface hydroxyl groups. This activated core is then added dropwise to heated polypropylene glycol diglycidyl ether. The activated core undergoes a nucleophilic ring-opening etherification reaction on the epoxy groups at one end of the polypropylene glycol diglycidyl ether, forming an intermediate with multiple long polyether arms radiating outwards from the core. A diethylenetriamine solution is obtained by mixing diethylenetriamine and propylene glycol monomethyl ether. The intermediate was added dropwise to a diethylenetriamine solution, where the polyamine groups rapidly initiated a complete nucleophilic ring-opening addition to the residual epoxy groups at the ends of the star-shaped polymer arms. In the final stage, deionized water was added, and the pH of the system was adjusted with glacial acetic acid, thereby preparing a diethylenetriamine-terminated hyperbranched polyglycerol-grafted polypropylene glycol diglycidyl ether star copolymer with excellent pigment wetting and dispersion potential.
[0015] According to a preferred embodiment of the present invention, in step B1, the polymerization time is 3-5 hours after heating to 100-105°C.
[0016] According to a preferred embodiment of the present invention, in step B2, the pH is adjusted to 7.0-7.5 using glacial acetic acid.
[0017] The present invention also provides a low-VOC environmentally friendly building interior wall coating composition prepared according to the preparation method of the low-VOC environmentally friendly building interior wall coating composition.
[0018] The beneficial effects of this invention are as follows: This invention designs and synthesizes N-(diaminoethyl)-aminopropylmethyldimethoxysilane-modified glycidyl methacrylate-polyetheramine-epoxidized soybean oil ring-opening copolymer (modified compound A) and diethylenetriamine-terminated hyperbranched polyglycerol-grafted polypropylene glycol diglycidyl ether star copolymer (modified compound B). Without adding volatile film-forming aids or organic solvents, it achieves synergistic improvements in multiple properties. In terms of environmental protection, this invention completely eliminates conventional film-forming aids such as alcohol esters and dodecyl alcohols, resulting in a product with low volatile organic compound content, truly solving the technical bottleneck of "difficulty in achieving both environmental performance and usability performance." In terms of functionality, this invention endows the coating with highly efficient and long-lasting indoor formaldehyde purification capabilities. Modified compound A, rich in primary and secondary amine groups, can undergo irreversible chemical addition reactions with formaldehyde in indoor air, fixing the formaldehyde within the paint film and preventing secondary release. Simultaneously, the alkoxysilane fragments in modified compound A undergo hydrolysis and condensation during paint film drying, generating a silicon-oxygen crosslinking network; the terminal amine groups of modified compound B undergo ring-opening crosslinking with the carboxyl and epoxy groups in the emulsion polymer. The synergistic effect of these two crosslinking mechanisms enables the paint film to form an organic-inorganic interpenetrating network structure, significantly improving the film's density, scrub resistance, hardness, and adhesion. Regarding processing and storage stability, the process of this invention is simple to operate and operates under mild conditions. All raw materials are commercially available industrial products, making it suitable for large-scale industrial production. This invention comprehensively solves the technical problems of existing low-VOC interior wall coatings, such as residual emissions of film-forming aids, lack of formaldehyde purification capabilities, insufficient mechanical properties of the paint film, and poor dispersion stability of pigments and fillers, from both molecular design and engineering application perspectives, demonstrating significant technological advancement. Detailed Implementation
[0019] The following detailed embodiments are only used to further illustrate this application and should not be construed as limiting the scope of protection of this application. Those skilled in the art can make some non-essential improvements and adjustments to this application based on the above application content.
[0020] Example 1
[0021] This embodiment provides a method for preparing a low-VOC environmentally friendly interior wall coating composition, the steps of which include: S1. Add 27.5g of deionized water to a stainless steel high-speed dispersion vessel. Maintain the vessel temperature at 25±2℃ by circulating cooling water through the vessel jacket. Turn on the dispersing agitator and adjust the speed to 400rpm. Add 1.25g of modified compound B (diethylenetriamine-terminated hyperbranched polyglycerol grafted polypropylene glycol diglycidyl ether star copolymer) and 0.25g of polyether-modified polysiloxane defoamer sequentially. Stir and disperse for 8 minutes until the system is homogeneous and free of lumps. Increase the stirring speed to 1000rpm and slowly add 20g of rutile titanium dioxide, 11.5g of calcined kaolin, 8.5g of heavy calcium carbonate, and 3.5g of talc in three batches, with a 3-minute interval between each batch. Avoid dust generation during the addition process. After all powders have been added, increase the stirring speed to 2000rpm and disperse and grind at high speed for 35 minutes. Samples were taken every 10 minutes, and the fineness was checked using a scraper fineness gauge. Grinding was stopped when the fineness was ≤40μm to obtain a uniform pigment and filler slurry.
[0022] S2. Reduce the stirring speed to 900 rpm and add 30 g of styrene-acrylic emulsion and 20 g of pure acrylic emulsion sequentially to the above pigment and filler slurry. In another beaker, mix 4.0 g of modified compound A (N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane-modified glycidyl methacrylate-polyetheramine-epoxy soybean oil ring-opening copolymer) with 4 g of methyl isobutyl ketone and stir magnetically at 300 rpm for 5 min until completely homogeneous and transparent. Add this mixture to the dispersion vessel at a rate of 2 mL / min through a constant pressure dropping funnel, maintaining stirring at 900 rpm during the addition, which takes approximately 4 min to complete. After the addition is complete, continue stirring for 25 min to ensure that modified compound A is uniformly dispersed in the emulsion system. While stirring at 500 rpm, add 0.75 g of associative polyurethane thickener and 0.25 g of 2-amino-2-methyl-1-propanol (AMP-95) to the system and continue stirring for 10 min. Measure the pH of the system using a precision pH meter. If it is not within the range of 8.75 ± 0.1, fine-tune it with deionized water until the final pH is 8.75. Add 0.25g of polyether-modified polysiloxane defoamer and 0.2g of 1,2-benzisothiazolin-3-one. Reduce the stirring speed to 300 rpm and slowly stir for 17.5 minutes to defoam until no obvious bubbles are visible on the coating surface. Stop stirring, discharge the material, and filter it through a 200-mesh filter to obtain the low-VOC environmentally friendly interior wall coating composition.
[0023] Preparation of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane-modified glycidyl methacrylate-polyetheramine-epoxidized soybean oil ring-opening copolymer (modified compound A): A1. Add 100g of epoxidized soybean oil and 125g of polyetheramine D-230 to a four-necked flask equipped with a reflux condenser, thermometer, constant pressure dropping funnel, and nitrogen inlet. Turn on the stirrer and set the speed to 200 rpm. Purge the air in the flask with high-purity nitrogen (flow rate 0.5L / min) for 15 minutes, maintaining a positive nitrogen pressure (0.02MPa). Heat the reaction vessel to 115℃ (oil bath temperature control ±1℃) and maintain the reaction at this temperature for 4 hours. During this period, take samples every 1 hour to measure the epoxy value until the epoxy value drops to less than 5% of the initial value, indicating that the ring-opening reaction between epoxidized soybean oil and polyetheramine is basically complete. Cool the reaction vessel to 85℃, add 0.06g of phenothiazine (PTZ) and 0.6g of triphenylphosphine (TPP) to the reaction system, and continue stirring for 10 minutes until completely dissolved. In another beaker, 20 g of glycidyl methacrylate (GMA) was dissolved in 30 g of methyl isobutyl ketone (MIBK), and the solution was transferred to a constant-pressure dropping funnel. Under nitrogen protection at 85 °C, the GMA / MIBK solution was slowly added dropwise at a rate of 0.5 mL / min, maintaining the reaction temperature at 85 ± 2 °C throughout the addition process, for a total addition time of approximately 60 min. After the addition was complete, the reaction was continued at 85 °C with stirring for 4 h. The characteristic peak of the epoxy group of GMA (910 cm⁻¹) was monitored using Fourier transform infrared spectroscopy. -1 The characteristic peak of the acrylate double bond (1635 cm⁻¹) disappeared, and at the same time, the characteristic peak of the acrylate double bond disappeared. -1 The mixture remained unchanged (phenothiazine effectively inhibited double bond polymerization), resulting in a pale yellow transparent mixture.
[0024] A2. Add 15g of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane (KH-602) and 50g of methyl isobutyl ketone to the above mixture. Adjust the reactor temperature to 70℃ and continue stirring for 4 hours under nitrogen protection. Gas chromatography is used to monitor the residual amount of KH-602; if it is less than 1%, the reaction is considered complete. After the reaction is complete, transfer the reaction mixture to a rotary evaporator. Set the water bath temperature to 60℃ and the vacuum degree to -0.095MPa. Remove the methyl isobutyl ketone by vacuum distillation until no fraction flows out, obtaining modified compound A.
[0025] Preparation of diethylenetriamine-terminated hyperbranched polyglycerol-grafted polypropylene glycol diglycidyl ether star copolymer (modified compound B): B1. Add 0.55 g pentaerythritol and 0.06 g sodium methoxide to a four-necked flask, install a reflux condenser, thermometer, constant-pressure dropping funnel, and nitrogen inlet, and introduce high-purity nitrogen (flow rate 0.3 L / min) to raise the temperature to 98 °C. Under nitrogen protection, add 12.5 g glycidyl ether dropwise through the constant-pressure dropping funnel at a rate of 0.2 mL / min, maintaining the reaction temperature at 99 °C during the dropwise addition, which takes approximately 60 min to complete. After the dropwise addition is complete, raise the reaction temperature to 103 °C and maintain the temperature for polymerization for 4 h. After polymerization, cool the reaction solution to 60 °C, add 7.5 g methanol to terminate the reaction, and stir for 15 min. Transfer the reaction mixture to a rotary evaporator and remove methanol and unreacted glycidyl ether by vacuum distillation at 50 °C and -0.095 MPa to obtain a hyperbranched polyglycerol (HPG) core. 1.75 g of the above-mentioned HPG core was dissolved together with 0.06 g of potassium hydroxide in 20 g of dipropylene glycol dimethyl ether (DMM). The mixture was activated at 60 °C and 200 rpm for 45 min with stirring, allowing KOH to fully abstract hydrogen from the HPG hydroxyl groups, generating alcohol-oxygen anions. 15 g of polypropylene glycol diglycidyl ether (PPG-DGE) was added to another 250 mL four-necked flask and heated to 90 °C. Under nitrogen protection, the activated HPG / DMM solution was added dropwise to the 90 °C PPG-DGE solution at a rate of 0.3 mL / min using a constant-pressure dropping funnel, maintaining the temperature at 90 ± 2 °C during the addition process. The addition was completed in approximately 70 min. After the addition was complete, the reaction was continued at 90 °C with stirring for 3 h. The epoxy value was monitored by epoxy titration until it dropped to below 15% of the initial value, yielding a star-shaped intermediate. In another beaker, 6.5 g of diethylenetriamine (DETA) and 11.5 g of propylene glycol monomethyl ether (PGME) were mixed and dissolved by magnetic stirring, and the mixture was heated to 60 °C. The star-shaped intermediate was transferred from the reaction vessel to a constant-pressure dropping funnel and added dropwise to the 60 °C DETA / PGME solution at a rate of 0.3 mL / min, maintaining the temperature at 60 ± 2 °C during the addition process. The addition was completed in approximately 90 min. After the addition was complete, the reaction was continued at 60 °C for 2 h to allow the residual epoxy groups at the ends of the intermediate to undergo a ring-opening addition reaction with the primary amine groups of DETA, yielding a reaction mixture with terminal amine functionalized groups.
[0026] B2. Transfer the above reaction mixture to a rotary evaporator and distill under reduced pressure at 55°C and -0.095 MPa to remove unreacted diethylenetriamine and some propylene glycol monomethyl ether until no obvious fraction remains. Add deionized water to the concentrated product to adjust the solid content to 32.5 wt% (standardized by drying and weighing). Adjust the pH to 7.25 dropwise with glacial acetic acid while stirring at 300 rpm (using a precision pH meter, measured at 25°C) to obtain modified compound B.
[0027] Example 2
[0028] The specific implementation method is the same as in Example 1, except that this example provides a method for preparing a low-VOC environmentally friendly interior wall coating composition, the steps of which include: S1. Add 20g of deionized water to the dispersion vessel; add 0.5g of modified compound B and 0.1g of polyether modified polysiloxane in sequence while stirring; add 15g of titanium dioxide, 8g of calcined kaolin, 5g of heavy calcium carbonate and 2g of talc powder, and grind for 30min to obtain pigment and filler slurry. S2. Add 25g of styrene-acrylic emulsion, 15g of acrylic emulsion, and a mixture containing 2.0g of modified compound A and 3g of methyl isobutyl ketone to the pigment and filler slurry, and stir. Add 0.3g of associative polyurethane thickener and 0.1g of 2-amino-2-methyl-1-propanol, and adjust the pH to 8.0. Add 0.1g of polyether-modified polysiloxane and 0.1g of 1,2-benzisothiazolin-3-one, stir, and degas for 15 minutes to obtain the coating.
[0029] Preparation of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane-modified glycidyl methacrylate-polyetheramine-epoxidized soybean oil ring-opening copolymer (modified compound A): A1. Mix 80g of epoxidized soybean oil and 100g of polyetheramine D-230, and react at 110℃ for 3h under nitrogen protection; cool to 80℃, add 0.02g of phenothiazine and 0.2g of triphenylphosphine, and dropwise add 20g of methyl isobutyl ketone containing 15g of glycidyl methacrylate, and continue to react at 80℃ for 3h to obtain a mixture; A2. Add 10g of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane and 40g of methyl isobutyl ketone to the mixture and react at 60℃ for 3h; distill under reduced pressure to obtain modified compound A.
[0030] Preparation of diethylenetriamine-terminated hyperbranched polyglycerol-grafted polypropylene glycol diglycidyl ether star copolymer (modified compound B): B1. Add 0.3g pentaerythritol and 0.02g sodium methoxide to a reaction vessel. Under nitrogen protection, heat to 95°C, add 10g glycidyl ether dropwise, heat to 100°C and polymerize for 3 hours. Add 5g methanol to obtain a hyperbranched polyglycerol core. Activate 1.0g of the hyperbranched polyglycerol core with 0.02g potassium hydroxide in 15g dipropylene glycol dimethyl ether. Add this to 15g polypropylene glycol diglycidyl ether preheated to 85°C and react for 2 hours to obtain an intermediate. Mix 5g diethylenetriamine and 8g propylene glycol monomethyl ether and heat to 55°C to obtain a diethylenetriamine solution. Add the intermediate dropwise to the diethylenetriamine solution and continue reacting for 1 hour to obtain the reaction mixture. B2. Add deionized water to the reaction mixture and adjust the pH to 7.0 with glacial acetic acid to obtain modified compound B.
[0031] Example 3
[0032] The specific implementation method is the same as in Example 1, except that this example provides a method for preparing a low-VOC environmentally friendly interior wall coating composition, the steps of which include: S1. Add 35g of deionized water to the dispersion vessel; add 2.0g of modified compound B and 0.4g of polyether-modified polysiloxane in sequence while stirring; add 25g of titanium dioxide, 15g of calcined kaolin, 12g of heavy calcium carbonate and 5g of talc powder, and grind for 40min to obtain pigment and filler slurry. S2. Add 35g of styrene-acrylic emulsion, 25g of acrylic emulsion, and a mixture containing 6.0g of modified compound A and 5g of methyl isobutyl ketone to the pigment and filler slurry, and stir. Add 1.2g of associative polyurethane thickener and 0.4g of 2-amino-2-methyl-1-propanol, and adjust the pH to 9.5. Add 0.4g of polyether-modified polysiloxane and 0.3g of 1,2-benzisothiazolin-3-one, stir, and degas for 20 minutes to obtain the coating.
[0033] Preparation of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane-modified glycidyl methacrylate-polyetheramine-epoxidized soybean oil ring-opening copolymer (modified compound A): A1. Mix 120g of epoxidized soybean oil and 150g of polyetheramine D-230, and react at 120℃ for 5h under nitrogen protection; cool to 90℃, add 0.10g of phenothiazine and 1.0g of triphenylphosphine, and dropwise add 40g of methyl isobutyl ketone containing 25g of glycidyl methacrylate, and continue to react at 90℃ for 5h to obtain a mixture; A2. Add 20g of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane and 60g of methyl isobutyl ketone to the mixture and react at 80℃ for 5h; distill under reduced pressure to obtain modified compound A.
[0034] Preparation of diethylenetriamine-terminated hyperbranched polyglycerol-grafted polypropylene glycol diglycidyl ether star copolymer (modified compound B): B1. Add 0.8g pentaerythritol and 0.10g sodium methoxide to a reaction vessel. Under nitrogen protection, heat to 100℃, add 15g glycidyl ether dropwise, heat to 105℃ for polymerization for 5h, add 10g methanol to obtain hyperbranched polyglycerol core; pre-dissolve 2.5g hyperbranched polyglycerol core and 0.10g potassium hydroxide in 25g dipropylene glycol dimethyl ether for activation, then add dropwise to 25g polypropylene glycol diglycidyl ether preheated to 95℃ and react for 4h to obtain an intermediate; mix 8g diethylenetriamine and 15g propylene glycol monomethyl ether, heat to 65℃ to obtain a diethylenetriamine solution; add the intermediate dropwise to the diethylenetriamine solution and continue the reaction for 3h to obtain the reaction mixture; B2. Add deionized water to the reaction mixture and adjust the pH to 7.5 with glacial acetic acid to obtain modified compound B.
[0035] Comparative Example 1 The specific implementation method is the same as in Example 1, except that no modified compound A is added, and the remaining components and amounts are exactly the same as in Example 1.
[0036] Comparative Example 2 The specific implementation method is the same as in Example 1, except that no modified compound B is added, and the remaining components and amounts are exactly the same as in Example 1.
[0037] Comparative Example 3 The specific implementation method is the same as in Example 1, except that modified compound A and modified compound B are not added, while the remaining components and amounts are exactly the same as in Example 1.
[0038] Performance testing The low-VOC environmentally friendly interior wall coating compositions prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance testing according to the following method, which included the following steps: Method for testing volatile organic compound (VOC) content: After stirring the coating to be tested evenly, weigh approximately 2g of the sample (accurate to 0.1mg) and place it in a pre-weighed aluminum foil dish. Dry the dish in a forced-air drying oven at (105±2)℃ for 1h. Remove the dish, cool it to room temperature in a desiccator, and weigh it. Calculate the non-volatile content. Take another approximately 2g of the sample, dilute it with an equal mass of deionized water, and determine the peak area of unreacted volatile organic compounds in the sample using a gas chromatograph (equipped with a flame ionization detector). Establish a calibration curve using n-hexane as a standard. Calculate the mass fraction of volatile organic compounds per unit mass of coating based on the non-volatile content and dilution ratio. Multiply this by the density of the coating (measured using a specific gravity bottle at (23±0.5)℃) to obtain the VOC mass per liter of coating, in g / L. Test each sample three times and take the arithmetic mean.
[0039] Formaldehyde purification efficiency test method: The coating to be tested is evenly coated onto five 500mm×500mm float glass plates using a wire bar coater, with a coating amount of (150±5) g / m². 2 Cured for 7 days at a temperature of (23±2)℃ and a relative humidity of (50±5)%. Three coated samples (two reserved as parallel samples) were placed in a 1m... 3In a sealed test chamber, the temperature was (23±2)℃ and the relative humidity was (50±5)%. Analytical-grade formaldehyde solution was injected into the chamber using a micro-syringe. The chamber fan was activated to ensure uniform formaldehyde evaporation. After 5 minutes, the initial formaldehyde concentration was measured using the acetylacetone spectrophotometric method at a detection wavelength of 412 nm. The initial concentration was controlled at (1.00±0.10) mg / m³. 3 Turn off the fan and seal the chamber for 24 hours. Then, sample again to measure the residual formaldehyde concentration. Calculate the formaldehyde purification efficiency using the following formula: Purification efficiency = (Initial concentration - Residual concentration) / Initial concentration × 100%, unit: %. Use the arithmetic mean of the purification efficiencies of the three samples as the test result.
[0040] Washability test method: The coating to be tested was applied to 5 asbestos-free fiber-reinforced cement boards (430mm×150mm×5mm), with a coating weight of (200±10) g / m². 2 The coating was applied in two coats, with a 24-hour interval between each coat, and cured for 28 days at a temperature of (23±2)℃ and a relative humidity of (50±5)%. The test panels were fixed on a scrubbing test machine. The scrubbing medium was a 0.5% (mass fraction) soap solution, and the scrubbing brush was a boar bristle brush. The contact load between the brush and the test panel was (450±10) g, and the scrubbing speed was (37±1) times / min (one reciprocating motion was counted as one stroke). During continuous scrubbing, the machine was stopped every 500 strokes to check whether the coating exposed the substrate, and the number of strokes at which the substrate was exposed was recorded. The median number of strokes achieved by at least three of the five test panels was taken as the test result, in units of strokes.
[0041] Pencil Hardness Test Method: The coating to be tested was applied to 6 float glass plates using a wire-stick applicator, controlling the dry film thickness to (40±5) μm, and cured for 7 days at a temperature of (23±2)℃ and a relative humidity of (50±5)%. A set of Zhonghua brand drawing pencils (hardness from 6B to 6H, a total of 14 grades) was prepared. The pencil lead was sharpened to a cylinder 5 mm long and 0.5 mm in diameter using a pencil sharpener. The tip of the pencil lead was then vertically ground smooth on 400-grit sandpaper until the edge was free of nicks. The coated sample was placed horizontally on a stable surface. Holding the pencil at a 45° angle to the paint film surface, the pencil was advanced approximately 6.5 mm at a speed of about 1 cm / s, making 3 marks at different locations for each hardness grade. Starting with the softest pencil, the hardness was gradually increased, and the paint film surface was observed for scratches (a continuous scratch ≥3 mm in length was considered a scratch). The hardness grade of the hardest pencil with at least 2 unscratched marks was used as the test result.
[0042] Adhesion test method: The coating to be tested was applied to three tinplates (120mm×50mm×0.3mm, surface sanded and degreased), with a dry film thickness of (50±10)μm. The coatings were cured for 7 days at a temperature of (23±2)℃ and a relative humidity of (50±5)%. A 10×10 grid (100 grids in total) with 1mm spacing was drawn on the paint film surface using a cross-cutting tool. The scratches should penetrate the paint film and reach the substrate. After removing debris from the scratches with a soft brush, transparent tape (adhesion strength (10±1)N / 25mm, width 25mm) was applied to the gridded area. The tape was pressed evenly with the fingers to ensure close contact with the paint film, eliminating air bubbles. Within (1.0±0.1)min, the free end of the tape was grasped and quickly peeled off at a 60° angle within 0.5s. According to the damage area classification: Level 0 is that the cut edge is completely smooth and there is no peeling; Level 1 is peeling area ≤5%; Level 2 is peeling area 5%~15%; Level 3 is peeling area 15%~35%; Level 4 is peeling area 35%~65%; Level 5 is peeling area ≥65%. The unit level is based on at least 2 out of 3 samples reaching the level.
[0043] Storage stability and viscosity change rate test method: The coating to be tested was placed into three 500mL sealed plastic containers (filled to 90% of the container volume) and stored in a constant temperature oven at (50±2)℃ for 30 days. Before and after storage, the viscosity of the coating was measured at (25±0.5)℃ using a rotational viscometer (using rotor No. 2, speed 6r / min). Each sample was measured three times and the average value was taken. After the storage period, the containers were removed, cooled to room temperature, and the presence of layering, precipitation, skinning, gelation, etc. was observed and recorded (Excellent: no layering, precipitation, skinning, gelation, viscosity change rate ≤10%; Good: slight layering but can be restored to uniformity after shaking, no hard precipitation, viscosity change rate 10%~20%; Medium: obvious layering or soft precipitation, viscosity change rate 20%~30%; Poor: skinning, gelation or hard precipitation, viscosity change rate >30%). The viscosity change rate is calculated using the following formula: Viscosity change rate = (Viscosity after storage - Initial viscosity) / Initial viscosity × 100%, in %, with the arithmetic mean of the viscosity change rates of 3 samples as the test result.
[0044] Test results: Table 1: Test results of each embodiment and comparative example VOC content (g / L) 3.2 2.8 3.8 2.9 3.1 2.7 Formaldehyde purification efficiency (%) 86.5 87.8 84.2 12.3 85.2 10.6 Washability (times) 8200 8500 7800 2400 3800 1300 Pencil hardness HB H B 2B B 3B Adhesion (Grade) 0 0 0 1 1 2 Storage stability (50℃ / 30d) excellent excellent excellent good middle middle Viscosity change rate (%) 5.2 4.8 6.1 12.5 18.3 22.6 As can be seen from Table 1, the test results of Examples 1-3 and Comparative Examples 1-3 show that, compared with Comparative Example 1 which only lacks modified compound A, the formaldehyde purification efficiency of Examples 1-3 has been greatly improved from 12.3% to over 84%, proving that modified compound A achieves efficient and irreversible chemical capture of formaldehyde through its polyamine structure, thus solving the technical problem of existing low-VOC coatings lacking active purification function.
[0045] Compared to Comparative Example 2, which only lacked modified compound B, Examples 1-3 showed improvements in scrub resistance from 3800 cycles to over 7800 cycles, pencil hardness from B to HB-H, adhesion from grade 1 to grade 0, storage stability from medium or good to excellent, and viscosity change rate from 18.3% to below 6%. This demonstrates that modified compound B, through its star-shaped topology and terminal polyamine groups, achieves efficient dispersion and stability of pigments and fillers, as well as participates in the crosslinking network of the paint film, thus solving the defects of low efficiency and insufficient mechanical properties of conventional dispersants.
[0046] Compared to Comparative Example 3, which lacked both modified compound A and modified compound B, Examples 1-3, while maintaining extremely low VOC (2.7-3.8 g / L), showed a significant increase in formaldehyde purification efficiency from 10.6% to over 84%, improved scrub resistance from 1300 cycles to over 7800 cycles, improved adhesion from level 2 to level 0, and improved storage stability from moderate to excellent. These examples comprehensively resolved the core contradiction in existing low-VOC coatings, which could not simultaneously achieve environmental friendliness, functionality (formaldehyde purification), and performance (scrub resistance, hardness, adhesion, and storage stability). This demonstrates that the two modified compounds have a significant synergistic effect.
[0047] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a low-VOC environmentally friendly interior wall coating composition, characterized in that the steps include... include: S1. Add 20-35 parts by weight of deionized water into the dispersion vessel; While stirring, add 0.5-2.0 parts of diethylenetriamine-terminated hyperbranched polyglycerol-grafted polypropylene glycol diglycidyl ether star copolymer and 0.1-0.4 parts of polyether-modified polysiloxane in sequence, and stir. Add 15-25 parts titanium dioxide, 8-15 parts calcined kaolin, 5-12 parts heavy calcium carbonate and 2-5 parts talc, grind to obtain pigment and filler slurry; S2. Add 25-35 parts of styrene-acrylic emulsion, 15-25 parts of acrylic emulsion, and a mixture containing 2.0-6.0 parts of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane-modified glycidyl methacrylate-polyetheramine-epoxy soybean oil ring-opening copolymer and 3-5 parts of methyl isobutyl ketone to the pigment and filler slurry. Stir, add 0.3-1.2 parts of associative polyurethane thickener and 0.1-0.4 parts of 2-amino-2-methyl-1-propanol, adjust the pH to 8.0-9.5, add 0.1-0.4 parts of polyether-modified polysiloxane and 0.1-0.3 parts of 1,2-benzisothiazolin-3-one, stir, and degas. The preparation method of the N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane modified glycidyl methacrylate-polyetheramine-epoxidized soybean oil ring-opening copolymer includes: A1. By weight, mix 80-120 parts of epoxidized soybean oil and 100-150 parts of polyetheramine, and react at 110-120℃ under nitrogen protection; cool to 80-90℃, add 0.02-0.10 parts of phenothiazine and 0.2-1.0 parts of triphenylphosphine, and dropwise add 20-40 parts of methyl isobutyl ketone containing 15-25 parts of glycidyl methacrylate, and continue the reaction at 80-90℃ to obtain a mixture; A2. Add 10-20 parts of N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane and 40-60 parts of methyl isobutyl ketone to the mixture, and react at 60-80℃; then distill under reduced pressure. The preparation method of the diethylenetriamine-terminated hyperbranched polyglycerol-grafted polypropylene glycol diglycidyl ether star copolymer includes: B1. By weight, add 0.3-0.8 parts pentaerythritol and 0.02-0.10 parts sodium methoxide to a reaction vessel. Under nitrogen protection, heat to 95-100℃, add 10-15 parts glycidyl ether dropwise, heat to 100-105℃ for polymerization, add 5-10 parts methanol to obtain a hyperbranched polyglycerol core; activate 1.0-2.5 parts of the hyperbranched polyglycerol core with 0.02-0.10 parts potassium hydroxide in 15-25 parts dipropylene glycol dimethyl ether, and add dropwise to 15-25 parts polypropylene glycol diglycidyl ether preheated to 85-95℃ to obtain an intermediate; mix 5-8 parts diethylenetriamine and 8-15 parts propylene glycol monomethyl ether, heat to 55-65℃ to obtain a diethylenetriamine solution; add the intermediate dropwise to the diethylenetriamine solution and continue the reaction to obtain a reaction mixture; B2. Add deionized water to the reaction mixture and adjust the pH with glacial acetic acid.
2. The method for preparing the low-VOC environmentally friendly interior wall coating composition according to claim 1, characterized in that, In step S1, the grinding time is 30-40 minutes.
3. The method for preparing the low-VOC environmentally friendly interior wall coating composition according to claim 1, characterized in that, In step S2, the degassing time is 15-20 minutes.
4. The method for preparing the low-VOC environmentally friendly interior wall coating composition according to claim 1, characterized in that, In step A1, the reaction continues at 80-90℃ for 3-5 hours.
5. The method for preparing the low-VOC environmentally friendly interior wall coating composition according to claim 1, characterized in that, In step A2, the reaction time is 3-5 hours at 60-80℃.
6. The method for preparing the low-VOC environmentally friendly interior wall coating composition according to claim 1, characterized in that, In step B1, the polymerization time is 3-5 hours after heating to 100-105℃.
7. The method for preparing the low-VOC environmentally friendly interior wall coating composition according to claim 1, characterized in that, In step B2, adjust the pH to 7.0-7.5 using glacial acetic acid.
8. A low-VOC environmentally friendly interior wall coating composition, characterized in that, The low-VOC environmentally friendly interior wall coating composition is prepared by the method according to any one of claims 1-7.
Citation Information
Patent Citations
Environment-friendly automotive interior coating and preparation method thereof
CN121227182A
Low-VOC environment-friendly building coating and preparation method thereof
CN121450171A